Discussion: Altruism, Spiritually Merging with a Fellow Human Being's Suffering - Turner, Edith L. B. (Zygon, 2006)
Abstract. This discussion focuses on the details of the wellsprings of altruism. The preceding articles in this section portray how spirit figures in various cultural guises appear in human lives with the gift of altruism, in a kind of seeding of the willing healer with the spirit's presence and its accompanying power of love, altruism, and healing. The word altruism is related to the French autre and autrui, “other,” with a special meaning here implying a relationship of identification.